2014
DOI: 10.1038/nrm3857
|View full text |Cite
|
Sign up to set email alerts
|

The maintenance of chromosome structure: positioning and functioning of SMC complexes

Abstract: Structural maintenance of chromosomes (SMC) complexes, which in eukaryotic cells include cohesin, condensin and the Smc5/6 complex, are central regulators of chromosome dynamics and control sister chromatid cohesion, chromosome condensation, DNA replication, DNA repair and transcription. Even though the molecular mechanisms that lead to this large range of functions are still unclear, it has been established that the complexes execute their functions through their association with chromosomal DNA. A large set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(188 citation statements)
references
References 165 publications
2
185
0
1
Order By: Relevance
“…This experiment demonstrates that label-free live cell imaging with SRS is a powerful method to examine chromosome dynamics during cell division. With this approach, it is also possible to observe nucleolus disassembly and reassembly, to determine the condensation level of DNA, and to monitor the movement of the chromosome during cell division, as well as other crucial cellular processes (25).…”
Section: Resultsmentioning
confidence: 99%
“…This experiment demonstrates that label-free live cell imaging with SRS is a powerful method to examine chromosome dynamics during cell division. With this approach, it is also possible to observe nucleolus disassembly and reassembly, to determine the condensation level of DNA, and to monitor the movement of the chromosome during cell division, as well as other crucial cellular processes (25).…”
Section: Resultsmentioning
confidence: 99%
“…However, no defects in TOP2A localization were observed, which corresponds to what has been reported for Smc5 cKO in mouse embryonic stem cells (Pryzhkova and Jordan, 2016). Studies of yeast SMC5/6 have shown that the complex is linked with TopoIIdependent catenation/decatenation functions (Jeppsson et al, 2014;Kanno et al, 2015;Kegel et al, 2011). Furthermore, meiotic depletion of Top2 in budding yeast affects Smc5 localization (Copsey et al, 2013).…”
Section: Smc5 Is a Maternal-effect Genementioning
confidence: 85%
“…The SMC5/6 complex contains the Nse2/Mms21 E3 SUMO ligase as well as Nse1, an E3 ubiquitin ligase, and the Nse3-6 subunits (Supplemental Fig. S5a; Jeppsson et al 2014). High-throughput yeast two-hybrid (Y2H) screens suggested that budding yeast Nse5 might bind Slx5 (Hazbun et al 2003), like its Schizosaccharomyces pombe homolog (Prudden et al 2007).…”
Section: The Soluble Mps3nmentioning
confidence: 99%